VARIASI BAHASA MURAL DI DAERAH ISTIMEWA YOGYAKARTA - Arif Purnomo; Basuki Basuki (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to determine (1) the form of mural language (2) describe the meaning of mural language and (3) the function of mural language in the Special Region of Yogyakarta. This is motivated by the phenomenal variety of mural languages. Variations in mural languages are usually tangible registers from each particular field. This type of research is descriptive qualitative research where very little or no calculations are used in it. The data in this study are the writings of murals and the context in the form of images in mural arts. The method of collecting data in this study is observation and documentation. The instrument of data research here is the researcher himself. While the data analysis process here uses the pragmatic method. From the description above, the results of mural language research in the Special Region of Yogyakarta are as follows; (1) Murals have variations in forms such as word forms, clauses, sentences, discourses, and even murals with dialogue forms. (2) Murals have meanings related to the social, cultural or cultural side, and politics. (3) Murals also have several functions, including conative functions that aim to give a suggestion to the reader or the partner. Fatigue function that wants to convey an emotional closeness to something. Referential functions that have the information side to the reader or partner. As well as the last emotive function that aims to convey the affective side in the form of feelings, be it feelings of sadness, joy or any other